A few steps along the road? Promoting support for parents with learning difficulties. (June 2015) - Tarleton, Beth; Williams, Val; Tarleton, Beth
<x xml:space="preserve">Abstract</x> Accessible summary Parents with learning difficulties often face lots of barriers to being the best parents they can. They often do not have the support they need. The Norah Fry Research Centre (NFRC) found out how to support parents with learning difficulties. It developed a network to help professionals work with parents with learning difficulties. Some professionals are working well with parents. Many professionals do not have the time, training or support they need to work with parents in a more positive way. Summary This paper considers the impact of research and development work around parenting by adults with a learning difficulty undertaken at the Norah Fry Research Centre (NFRC) since 2005. It discusses how our understanding of the support needs of parents with learning difficulties grew through an initial mapping study which led to the concept of 'Parenting with Support'. It then discusses the development of the Working Together with Parents Network which has endeavoured to continue to draw together and promote positive support for parents with learning difficulties and how the subsequent research at NFRC has been undertaken with a desire to further understand and support the development of this positive practice. It describes how this work has supported professionals already aware of parents with learning difficulties' support needs and but has yet to engage with the far wider range of professionals and agendas involved in supporting vulnerable families.